Comprehensive Analysis of CD4+ T Cell Response Cross-Reactive to SARS-CoV-2 Antigens at the Single Allele Level of HLA Class II - Hyun, You-Seok; Lee, Yong-Hun; Jo, Hyeong-A; Baek, In-Cheol; Kim, Sun-Mi; Sohn, Hyun-Jung; Kim, Tai-Gyu (Frontiers in Immunology, 2022)
Common human coronaviruses have been circulating undiagnosed worldwide. These common human coronaviruses share partial sequence homology with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); therefore, T cells specific to human coronaviruses are also cross-reactive with SARS-CoV-2 antigens. Herein, we defined CD4+ T cell responses that were cross-reactive with SARS-CoV-2 antigens in blood collected in 2016–2018 from healthy donors at the single allele level using artificial antigen-presenting cells (aAPC) expressing a single HLA class II allotype. We assessed the allotype-restricted responses in the 42 individuals using the aAPCs matched 22 HLA-DR alleles, 19 HLA-DQ alleles, and 13 HLA-DP alleles. The response restricted by the HLA-DR locus showed the highest magnitude, and that by HLA-DP locus was higher than that by HLA-DQ locus. Since two alleles of HLA-DR, -DQ, and -DP loci are expressed co-dominantly in an individual, six different HLA class II allotypes can be used to the cross-reactive T cell response. Of the 16 individuals who showed a dominant T cell response, five, one, and ten showed a dominant response by a single allotype of HLA-DR, -DQ, and -DP, respectively. The single allotype-restricted T cells responded to only one antigen in the five individuals and all the spike, membrane, and nucleocapsid proteins in the six individuals. In individuals heterozygous for the HLA-DPA and HLA-DPB loci, four combinations of HLA-DP can be expressed, but only one combination showed a dominant response. These findings demonstrate that cross-reactive T cells to SARS-CoV-2 respond with single-allotype dominance.